Pengaruh Prenatal Yoga Terhadap Keadaan Emosi Ibu Hamil di PMB Appi Amelia - Kusumaningtyas, Bernadetta; Utami, Nendhi Wahyunia (MEDIA ILMU KESEHATAN, 2025)
Background: Most pregnant women are worried about discomfort, especially during labor, which makes them more sensitive to emotional changes. An alternative that can improve health and reduce stress is exercising. Prenatal yoga is used as a way to manage overall stress and as a treatment for anxiety or depression.Objective: To determine prenatal yoga effect on emotional state of pregnant women. Methods: Quantitative research method with a One-Group Pretest-Posttest design was employed, involving 18 pregnant respondents selected through purposive sampling technique. Primary data collection was conducted by distributing the DASS 42 questionnaire, and bivariate data analysis was performed using the Wilcoxon test.Results: The average (mean) levels of stress, anxiety, and depression showed a significant decrease, from 11.11 to 4.50 in the stress category, from 9.17 to 3.44 in the anxiety category, and from 1.67 to 0.28 in the depression category. The Wilcoxon test revealed a p-value of 0.007 in the stress category, 0.001 in the anxiety category, and 0.371 in the depression category.Conclusion: The decrease in the average score of emotional state levels in each category indicates the influence of prenatal yoga on the emotional state of pregnant women.